Nanotechnology Attitude Scale Development Study for Pre-Service Science Fields Teachers - Tuba Şenel Zor; Adnan Kan (Journal of Science Learning, 2021)
This study aims to develop a measurement tool to measure pre-service teachers' attitudes (PST) in science fields towards nanotechnology. For this purpose, a five-point Likert-type scale consisting of 55 items applied to 373 PST who enrolled in science fields (Science, Chemistry, Biology, Physics) at the grades 1st, 2nd, 3rd, and 4th at a public university in Turkey. The exploratory factor analysis (EFA) determined that the scale had a 3-factor structure consisting of 24 items and the factors explained 55.854% of the total variance of the attitude variable. Verification of the model was tested by applying confirmatory factor analysis (CFA). The CFA data obtained from 770 PST enrolled in science fields at the grades 1st, 2nd, 3rd, and 4th at two different public universities in Turkey. The results obtained from CFA were in agreement with the model obtained by EFA. Cronbach's alpha (Cr-α) reliability of the scale calculates to be 0.926. Findings from the validity and reliability analyses show that the scale is a valid and reliable measurement tool that can measure pre-service science fields teachers’ (PSSFT) attitudes towards nanotechnology.